The Impact of Government Accounting Standards Implementation, Internal Control Systems, and Accounting Information Systems Utilization on Financial Report Quality at the Investment and Integrated One-Stop Services Office of West Java Province - Hadi, Norman; Windiarti, Sofia (Dinasti Publisher, 2025)
This research examines the impact of three elements - Government Accounting Standards (GAS), Internal Control Systems (ICS), and the utilization of Accounting Information Systems (AIS) on the accuracy of financial reporting at the Investment and Integrated One-Stop Services Office (DPMPTSP) in West Java Province. The researchers employed a quantitative methodology, selecting 30 participants from 194 total staff members through purposive sampling. The researchers analyzed the data using a technique known as Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. The outcomes indicate that out of the three factors examined, only the use of Accounting Information Systems has a significant influence on the quality of financial reports (with statistical significance at p-value < 0.05). Government Accounting Standards implementation and Internal Control Systems did not show any significant impacts. The R² value of 0.906 in the research indicates that 90.6% of the variation in financial report quality is explained by these three variables working together. The results suggest that enhancing accounting information system usage is the primary driver for improving financial reporting quality within government organizations. The implementation of government accounting standards and internal control systems need to be reviewed and strengthened so that their contribution to the quality of financial reporting becomes more significant.